Triggered Firing and Atrial Fibrillation in Transgenic Mice With Selective Atrial Fibrosis Induced by Overexpression of TGF-β1 - Choi, Eue-Keun (2012)
BACKGROUND: Calcium transient triggered firing (CTTF) is induced by large intracellular calcium (Ca(i)) transient and short action potential duration (APD). We hypothesized that CTTF underlies the mechanisms of early afterdepolarization (EAD) and spontaneous recurrent atrial fibrillation (AF) in transgenic (Tx) mice with overexpression of transforming growth factor β1 (TGF-β1). METHODS AND RESULTS: MHC-TGFcys(33)ser Tx mice develop atrial fibrosis because of elevated levels of TGF-β1. We studied membrane potential and Ca(i) transients of isolated superfused atria from Tx and wild-type (Wt) littermates. Short APD and persistently elevated Ca(i) transients promoted spontaneous repetitive EADs, triggered activity and spontaneous AF after cessation of burst pacing in Tx but not Wt atria (39% vs. 0%, P=0.008). We were able to map optically 4 episodes of spontaneous AF re-initiation. All first and second beats of spontaneous AF originated from the right atrium (4/4, 100%), which is more severely fibrotic than the left atrium. Ryanodine and thapsigargin inhibited spontaneous re-initiation of AF in all 7 Tx atria tested. Western blotting showed no significant changes of calsequestrin or sarco/endoplasmic reticulum Ca(2+)-ATPase 2a. CONCLUSIONS: Spontaneous AF may occur in the Tx atrium because of CTTF, characterized by APD shortening, prolonged Ca(i) transient, EAD and triggered activity. Inhibition of Ca(2+) release from the sarcoplasmic reticulum suppressed spontaneous AF. Our results indicate that CTTF is an important arrhythmogenic mechanism in TGF-β1 Tx atria.